Ultra-Deep Dolomite Reservoir Quality Classification and its Effect on Acid-Fracturing Based on Natural Fracture Activity Analysis: A Case Study of the Cambrian Subsalt Reservoir in Northern Uplift of Tarim Basin - Yin, Guoqing; Zhang, Hui; Xin, Yi; Zhang, Wei; Wu, Xingneng; Liang, Jingrui; Lai, Shujun (Frontiers in Earth Science, 2022)
Taking the >8000 m buried Cambrian subsalt dolomite reservoir in Northern uplift of Tarim Basin as an example, this study used the imaging logging, cores, outcrops, and other data to identify natural fractures, obtained parameters of natural fractures, including strike, azimuth, width, length, and apparent porosity, and clarified the characteristics of natural fractures in well section. Based on logging data, the wellbore rock mechanics, in-situ stress, elastic parameters were established. The analysis of the mechanical characteristics of natural fractures was carried out to find out the shear stress, normal stress, and their ratio of each natural fracture in the reservoir section. Combined with the stress value of each fracture, the quantitative characterization parameter(FGAI) of the mechanical characteristics of natural fractures is established. Combined with the petrophysical parameters of natural fractures, the evaluation model of the quality index of the reservoir containing natural fractures is established. According to the classification of the quality of the reservoir, combined with the petrophysical properties of the reservoir section, the optimization of the acid fracturing scheme and the injection pressure are carried out, so as to realize the production increase of acid-fracturing. In the study, the quality of reservoirs with natural fractures is divided into three categories: Class I reservoir QRCF is 0.6~1, Class II reservoir is 0.3~0.6, and Class III reservoir QRCF is less than 0.3. The application of Well L1 and other wells shows that there are great differences in the development of natural fractures at different depths of Cambrian subsalt dolomite reservoir, so as to the QRCF. Class I reservoir is easy for acid-fracturing to achieve a high performance. Class II reservoir needs the application of large-scale acid-fracturing, and Class III reservoir cannot be subjected to acid-fracturing based on the current process measures. The research results provide a reference for the classification of fracture mechanical activity of ultra-deep Cambrian subsalt dolomite reservoir and the optimization of acid-fracturing reformation parameters of similar reservoirs.